WHO risk chart associated with the presence of coronary plaque on coronary computed tomographic angiography in asymptomatic indonesian population - Indrihapsari, Pratiwi; Saskia Dyah Handari; Cholid Tri Tjahjono (Universitas Brawijaya, 2025)
Background: Cardiovascular risk assessment tools, like the WHO Risk Chart, often categorize asymptomatic individuals as low risk, even when they have unmanaged cardiovascular risk factors. Among these patients, estimation of CAD is associated with significant differences in CACS; however, the relationship between WHO Risk Chart and CACS has not been studied. Objective: We studied WHO Risk Chart’s ability to detect for coronary plaque throughout CACS via CCTA. Methods: A total of 440 subjects aged 40 to 74 years old, who underwent CCTA for health checkup between January 2023 and December 2024 were enrolled. Clinical information was gathered from medical records, including risk factors, CACS, and CCTA results. Statistical analysis was performed using SPSS 24, applying univariate, bivariate, and multivariate regression analyses to identify correlations. Results: The WHO Risk Chart showed a significant correlation with CACS and the presence of coronary plaque (p <0.05). In total, 148 individuals were identified with normal coronary arteries, while 292 individuals presented with coronary plaque. Notable differences were found among genders, WHO Risk Chart, smoking status, hypertension, dyslipidemia, diabetes mellitus, and CACS levels between the two groups (p<0.05). The correlation coefficient suggests that an increase in the WHO Risk Chart is associated with a rise in CACS, indicating a bidirectional relationship between these two parameters. Conclusion: In an asymptomatic population from Indonesia, the WHO Risk Chart shows a strong positive correlation with CACS.